Making Sense of Camp Delta - Joseph Margulies (Washington University Journal of Law & Policy, 2007)
In the pages that follow, I want to do two things. First, I hope to describe the Administration’s detention policy in general, and Camp Delta in particular, from the Administration’s perspective. I am not part of the crowd of people who believe the President should be impeached; that members of his Administration should be indicted as war criminals; that John Yoo, the author of the infamous “torture memo” should be disbarred from the practice of law; and that the detention policy is itself an inexplicable assault on the rule of law. While I am certainly no defender of the policy (in fact, my colleagues and I have fought it tooth and nail for more than six years), I think it has a rationale which we must endeavor to understand, because we cannot mount a nuanced critique of the policy without first acquiring an equally nuanced grasp of its purpose. And second, having described what the Administration had in mind with Camp Delta, I want to explore some of the assumptions embedded in the Administration’s thinking, so that we may discuss whether, in light of known facts and subsequent events, those assumptions are valid.
Keywords: War on Terrorism; 2001-2009 -- Social aspects; Military policy; Detention of persons; Coercive interrogation; George W. Bush Administration; Guantánamo Bay; Cuba; Terrorists; Torture; United States